On the predominance of unstable atmospheric conditions in the marine boundary layer offshore of the U.S. northeastern coast. Issue 15 (9th August 2016) - Archer, Cristina L.; Colle, Brian A.; Veron, Dana L.; Veron, Fabrice; Sienkiewicz, Matthew J.
Abstract: The marine boundary layer of the northeastern U.S. is studied with focus on wind speed, atmospheric stability, and turbulent kinetic energy (TKE), the three most relevant properties in the context of offshore wind power development. Two long‐term observational data sets are analyzed. The first one consists of multilevel meteorological variables measured up to 60 m during 2003–2011 at the offshore Cape Wind tower, located near the center of the Nantucket Sound. The second data set comes from the 2013–2014 IMPOWR campaign (Improving the Modeling and Prediction of Offshore Wind Resources), in which wind and wave data were collected with new instruments on the Cape Wind platform, in addition to meteorological data measured during 19 flight missions offshore of New York, Connecticut, Rhode Island, and Massachusetts. It is found that, in this region: (1) the offshore wind resource is remarkable, with monthly average wind speeds at 60 m exceeding 7 m s −1 all year round, highest winds in winter (10.1 m s −1 ) and lowest in summer (7.1 m s −1 ), and a distinct diurnal modulation, especially in summer; (2) the marine boundary layer is predominantly unstable (61% unstable vs. 21% neutral vs. 18% stable), meaning that mixing is strong, heat fluxes are positive, and the wind speed profile is often nonlogarithmic (~40% of the time); and (3) the shape of the wind speed profile (log versus nonlog) is an effective qualitative proxy for atmospheric stability, whereas TKE alone is not. Key Points: The marine boundary layer offshore of the northeastern U.S. is predominantly unstable Nonlogarithmic wind speed profiles are a valid proxy for unstable offshore conditions Stable conditions offshore of the northeastern U.S. occur mostly in spring and with southwesterly flow